Cases Study of patients that come to centeral heart and interpenetrate compulsion from January 2013 to Juni 2013 - حسن وداعه قاسم (University of Thi-Qar Journal of Science, 2016)
Collecte 978 samples from patients that come to centeral heart from January 2013 to juni 2013 at defferent agesand deffrent genus ,the high infection s left cut 355 case s (263 at male ,92 at femal,the low cases left cut and right cut the number (63 cases (53 at male and 10 at femal ),the high number 407 patients at percentage 41.61% at age s between 56-65 year (301 at male and 106 at female) and low number at age 86 year (3 patients .The total good health 591 patients (396 male at percentage 67.1% and 915 female at percentage 32.99% the artery 143 (112 male and 31 female and the good health 243 (183 male and 60 female)And not any thing 268 (166 male and 102 female ,left and right cut 63 patient (53 in male and 10 in female, Rhigt cut (150 (115 male and 35 female .The aim of study to identification desease of heart at the patient that come to heart centeral deseases from January 2013 to Juni 2013 .